Agama sebagai Religiositas Masyarakat dalam Dunia Kehidupan Modern: Studi Kolaburatif Antropologi Agama dan Pandangan Filosofis Habermas Tentang Agama - Zandro, Agrindo (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
This study discusses the appreciation of religious religiosity in modern society and how religion as a religiosity of society plays a role in the world of modern life. Jürgen Habermas argues that religion is a social fact that has never disappeared from human civilization even though the world has experienced various changes in secular modern civilization. People still pray diligently and carry out various teachings from religion. But today, religion is questioned because it does not have a meaningful contribution to the world. For this reason, this study will explore religion as religiosity so that a contribution to the world of universal life can be found. This study uses qualitative research methods by applying literature studies. The object of study of this study is analyzed collaboratively; analyzing religion from an anthropological point of view and collaborated with Jürgen Habermas' philosophical views on religion. By applying a collaborative study, this study finds that religion as religiosity has a functional and substantial capacity to restore life in the midst of modernity that has lost its human orientation. The contribution of this study is some principles that must be considered in religion as an orientation in the pace of development of an increasingly modern world.